The Role of Emotional Regulation as a Mediator of Self-Compassion and Stress in Students Completing Final Assignments - Rahmayanti, Fitria Dian; Nashori, Fuad (International Journal of Islamic Educational Psychology, 2024)
Final semester students must complete their education on time with a variety of academic assignments. Apart from that, the personal problems they experience are also increasingly complex, making final-semester students vulnerable to depression. This research aims to determine the relationship between self-compassion and stress mediated by emotional regulation in students who complete their final assignments. The design used in this research was quantitative, with three variables. Data were collected using the Self-Compassion Scale with a Cronbach Alpha reliability of 0.872, the Emotion Regulation Questionnaire (ERQ) with a Cronbach Alpha reliability of 0.790, and the stress subscale of the Depression Anxiety Stress Scale (DASS-42) with a Cronbach Alpha reliability of 0.951. The subjects of this research were final-year students who were pursuing higher education in the Special Region of Yogyakarta. Data analysis used a mediation analysis model by testing the relationship between stress (dependent variable) and self-compassion (independent variable) and emotional regulation, cognitive reappraisal facets, and expressive suppression facets (mediator variables) using mediation analysis techniques via JASP. The results showed that the cognitive reappraisal facet of emotional regulation mediated the relationship between self-compassion and stress in students. The emotional regulation facet of expressive suppression did not mediate the relationship between self-compassion and stress in students. In addition, there was a direct negative relationship between self-compassion and stress. Students who complete their final assignment must make efforts to increase self-compassion in order to survive stressful situations.